3D curved glass-ceramics, chemically strengthened glass-ceramics, and their preparation and application
By adjusting the oxide content ratio and specific heat treatment processes, the problems of poor optical and insufficient mechanical strength in mass production of 3D curved microcrystalline glass are solved, and the optical and mechanical properties of the product are excellent.
Patent Information
- Application Number
- CN202311801461.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-12-25
Smart Images

Figure CN117776536B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of glass technology, and specifically relates to a 3D curved microcrystalline glass, chemically strengthened microcrystalline glass, and a preparation method and application thereof. Background Art
[0002] With the development of electronic display technology, glass has gradually replaced plastic materials and is used in display devices as a protective cover material. At the same time, with the diversified application of electronic products, 3D curved screens such as curved screen mobile phones and smart watches are gradually becoming popular. Among them, 3D curved microcrystalline glass has gradually attracted industry attention due to its superior strength performance over ordinary 3D curved glass.
[0003] The mass production of 3D curved glass-ceramics for display screens with high requirements for optical display effects is quite difficult. A major reason is that when producing large-sized prefabricated glass-ceramics for the preparation of 3D curved glass-ceramics, it is difficult to ensure the uniformity of the composition and the uniformity of the temperature field, and it is easy to produce prefabricated glass-ceramics with poor local optics. Moreover, this problem still exists after the prefabricated glass-ceramics are heat-bent, which leads to the 3D curved glass-ceramics having undesirable colors in parts or uneven display effects as a whole, and even easy to cause fragmentation during the heat-bending process.
[0004] It should be noted that this part of the present application only provides background technology related to the present application and does not necessarily constitute prior art or known technology. Summary of the invention
[0005] In order to increase output, when the production line mass produces 3D curved microcrystalline glass with petalite and lithium disilicate crystal phase structure, it generally produces large-sized substrate glass bricks first, such as substrate glass bricks with length, width and thickness specifications of (200mm-500mm)×(100mm-500mm)×(10mm-40mm). The substrate glass bricks are then heat-treated to obtain prefabricated microcrystalline glass products. Considering that the microcrystalline glass of this system is usually accompanied by a certain degree of crystallization during the hot bending process, the degree of crystallization of the obtained prefabricated microcrystalline glass products is generally lower than that of the final 3D curved microcrystalline glass products. The prefabricated microcrystalline glass products are then cold-processed to prepare multiple flat microcrystalline glass sheets of required specifications and sizes. After that, the obtained flat microcrystalline glass sheets are hot-bent to obtain 3D curved microcrystalline glass products.
[0006] However, the existing microcrystalline glass solutions with petalite and lithium disilicate as the main crystal phases are prone to poor optical properties of prefabricated microcrystalline glass bricks when mass-producing large-sized prefabricated microcrystalline glass products. The main manifestation is that the b-values of different regions in the prefabricated microcrystalline glass bricks are quite different, and the local areas show undesirable colors and are prone to flowery pieces. This difference cannot be improved through the subsequent hot bending process, resulting in large differences in b-values of different regions in the 3D curved microcrystalline glass obtained through the hot bending process, which in turn affects the overall display effect of the 3D curved microcrystalline glass, making it difficult for the prepared 3D curved microcrystalline glass to meet the application requirements of the display cover. Some prefabricated microcrystalline glass products even break during the hot bending process, resulting in a decrease in yield.
[0007] The purpose of the present application is to overcome the problems in the prior art of low mass production yield and easy occurrence of flowery and poor display of 3D curved microcrystalline glass products whose main crystal phases are petalite crystal phase and lithium disilicate crystal phase, and to provide a 3D curved microcrystalline glass, and provide a preparation method and application thereof.
[0008] In order to achieve the above purpose, the following technical solutions are provided:
[0009] 1. A 3D curved glass-ceramic, wherein the 3D curved glass-ceramic contains a petalite crystalline phase and a lithium disilicate crystalline phase, wherein the petalite crystalline phase and the lithium disilicate crystalline phase have a higher weight percentage than other crystalline phases present in the 3D curved glass-ceramic;
[0010] Measured in terms of molar percentage of oxides, the composition of the 3D curved glass-ceramics includes:
[0011] SiO2: 60.00mol%-71.00mol%, Al2O3: 1.50mol%-5.00mol%, P2O5: 0.80mol%-1.50mol%, ZrO2: 2.00mol%-4.00mol%, Na2O: 0.00m ol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-30.00mol%, CaO: 0.00mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%;
[0012] The composition of the 3D curved glass-ceramics satisfies the following conditions, measured by the content of each oxide in the composition of the 3D curved glass-ceramics expressed in molar percentage:
[0013] 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250;
[0014] 18.200≤Li2O / P2O5≤25.500;
[0015] 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.200;
[0016] 1.500≤10×(ZrO2+P2O5) / Li2O≤2.000;
[0017] 4.000≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤6.000. When the content of each oxide is within an appropriate range and in combination with the content ratio of the oxide under specific conditions, the generation of the main crystalline phase can be ensured in the process of mass production of 3D curved glass-ceramics products. At the same time, the prepared 3D curved glass-ceramics products can be ensured to present a relatively uniform display effect as a whole, effectively avoiding the problem of large differences in b values in different regions of mass-produced 3D curved glass-ceramics products and poor display effects.
[0018] It should be pointed out that in the above formulas of the present application, the percentage of content in moles is substituted into each formula, that is, the molar unit does not participate in the calculation of the formula. For example, if the molar content of P2O5 is 0.80%, 0.80% is substituted into the formula for calculation.
[0019] 2. The 3D curved glass-ceramics according to technical solution 1, wherein the composition of the 3D curved glass-ceramics, measured by the content expressed by mole percentage of each oxide in the composition of the 3D curved glass-ceramics, satisfies:
[0020] 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤5.000;
[0021] 12.200≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.000. Further adjusting the content relationship between the components is conducive to ensuring that the 3D curved glass-ceramics obtains excellent optical properties and mechanical strength properties.
[0022] 3. The 3D curved glass-ceramic according to technical solution 1 or 2, wherein the 3D curved glass-ceramic is transparent in the visible light range. By making the 3D curved glass-ceramic transparent in the visible light range, it can meet the use requirements of the display screen, which helps to broaden the application fields and application scenarios of the 3D curved glass-ceramic.
[0023] 4. The 3D curved glass-ceramic according to any one of technical solutions 1 to 3, wherein the composition of the 3D curved glass-ceramic, measured in terms of molar percentage of oxides, comprises:
[0024] SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: not less than 0.85mol% and less than 1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: greater than 0.00mol% and less than 1.00mol%, K2O: greater than 0.00mol% and less than 0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: greater than 0.50mol% and less than 1.50mol%, B2O3: 0.00mol%-1.00mol%. By adjusting the content relationship of the necessary oxides, it is beneficial to further improve the network structure of the 3D curved microcrystalline glass, thereby ensuring the large-scale mass production effect of the prefabricated microcrystalline glass and ensuring the excellent optical properties and strength properties of the mass-produced 3D curved microcrystalline glass products.
[0025] 5. The 3D curved glass-ceramic according to any one of technical solutions 1 to 4, wherein the 3D curved glass-ceramic does not contain a quartz crystal phase. By avoiding the precipitation of a quartz crystal phase in a 3D curved glass-ceramic whose main crystal phases are a petalite crystal phase and a lithium disilicate crystal phase, it is helpful to ensure the optical performance and overall uniformity of the 3D curved glass-ceramic.
[0026] 6. A 3D curved glass-ceramic according to any one of technical solutions 1-5, wherein the total content of the petalite crystal phase and the lithium disilicate crystal phase in the 3D curved glass-ceramic accounts for more than 60.00wt% of the mass of the 3D curved glass-ceramic, preferably more than 70.00wt%, and more preferably more than 80.00wt%; in the 3D curved glass-ceramic, the average crystal size does not exceed 100nm. A higher content of the main crystalline phase is beneficial to improving the mechanical strength performance of the 3D curved glass-ceramic. A smaller average crystal size is beneficial to ensuring the excellent optical properties of the 3D curved glass-ceramic.
[0027] 7. The 3D curved glass-ceramics according to any one of technical solutions 1 to 6, wherein the composition of the 3D curved glass-ceramics, measured by the content expressed by mole percentage of each oxide in the composition of the 3D curved glass-ceramics, satisfies:
[0028] 0.184≤5×P2O5 / (Li2O+0.5Al2O3)≤0.245; and / or
[0029] 18.200≤Li2O / P2O5≤25.000; and / or
[0030] 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.180; and / or
[0031] 1.500≤10×(ZrO2+P2O5) / Li2O≤1.900; and / or
[0032] 4.200≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤5.900; and / or
[0033] 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤4.950; and / or
[0034] 15.000≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.000.
[0035] 8. The 3D curved glass-ceramics according to any one of technical solutions 1 to 7, wherein the composition of the 3D curved glass-ceramics, expressed in terms of the molar percentage of each oxide in the composition of the 3D curved glass-ceramics, satisfies:
[0036] 0.186≤5×P2O5 / (Li2O+0.5Al2O3)≤0.243; and / or
[0037] 18.500≤Li2O / P2O5≤24.700; and / or
[0038] 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.170; and / or
[0039] 1.550≤10×(ZrO2+P2O5) / Li2O≤1.850; and / or
[0040] 4.600≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤5.850; and / or
[0041] 2.680≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤4.930; and / or
[0042] 16.000≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.000.
[0043] 9. The 3D curved glass-ceramic according to any one of technical solutions 1 to 8, wherein when the thickness is 0.6 mm, the optical b value of the 3D curved glass-ceramic is ≤1.00, preferably the optical b value is ≤0.70, and more preferably the optical b value is ≤0.55. The smaller the b value, the better the optical performance of the 3D curved glass-ceramic and the better the overall display effect.
[0044] 10. The 3D curved glass-ceramic according to any one of technical solutions 1 to 9, wherein, when the thickness is 0.6 mm, the range of the b value at nine locations on the main surface of the 3D curved glass-ceramic is ≤0.30, preferably the range of the b value at nine locations on the main surface is ≤0.10, and more preferably the range of the b value at nine locations on the main surface is ≤0.06. The smaller the range of the b value at nine locations on the main surface of the 3D curved glass-ceramic sheet of this specification, the better the overall uniformity of the 3D curved glass-ceramic sheet of the present application, and the better the overall display effect.
[0045] The nine positions are: (1) the test positions of test circle I close to the four corners of the main surface, a total of four positions; (2) the test positions of four test circles II formed by the points on the line segment formed by the centers of the four test circles I that are closest to the middle of the long side or short side of the main surface, a total of four positions; (3) the position of a test circle III formed by the center point of the main surface as the center of the circle.
[0046] 11. A substrate glass, which can be used to prepare the 3D curved glass-ceramics as described in any one of technical solutions 1 to 10, wherein the composition of the substrate glass, in terms of molar percentage of oxides, includes:
[0047] SiO2: 60.00mol%-71.00mol%, Al2O3: 1.50mol%-5.00mol%, P2O5: 0.80mol%-1.50mol%, ZrO2: 2.00mol%-4.00mol%, Na2O: 0.00m ol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-30.00mol%, CaO: 0.00mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%;
[0048] The composition of the substrate glass satisfies the following conditions, expressed in terms of the molar percentage of each oxide in the substrate glass composition:
[0049] 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250;
[0050] 18.200≤Li2O / P2O5≤25.500;
[0051] 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.200;
[0052] 1.500≤10×(ZrO2+P2O5) / Li2O≤2.000;
[0053] 4.000≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤6.000;
[0054] 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤5.000;
[0055] 12.200≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.000. By making the substrate glass meet the above composition requirements, it is not only possible to ensure that the substrate glass bricks are in a good melting condition, but also possible to prepare prefabricated microcrystalline glass bricks with good overall uniformity, good display effect, excellent optical properties, excellent mechanical properties, and main crystal phases of petalite crystal phase and lithium disilicate crystal phase, which is conducive to hot bending to obtain 3D curved microcrystalline glass products with excellent optical and mechanical properties.
[0056] 12. The substrate glass according to technical solution 11, wherein: after synchronous thermal analysis test, in a nitrogen protective atmosphere, the substrate glass is heated from room temperature to 900°C at a heating rate of 10°C / min to obtain a heating DSC curve, in which there are at least two exothermic peaks, wherein the first exothermic peak temperature T1 is 600°C-730°C, and the second exothermic peak temperature T2 is 740°C-800°C, and T1 and T2 satisfy the relationship: 100°C ≥ T2-T1 ≥ 40°C, preferably 80°C ≥ T2-T1 ≥ 50°C. Large-sized substrate glass bricks made of substrate glass solutions that meet specific DSC curve characteristics are heat-treated under the production line process conditions of mass production of microcrystalline glass to obtain prefabricated microcrystalline glass bricks whose optical properties and display effects meet the requirements for display screens, which can well solve the problems of large differences in b values in different areas of glass bricks, localized undesirable colors, flower pieces, poor display, etc. that are easy to occur in the mass production of prefabricated microcrystalline glass bricks in the prior art.
[0057] 13. The substrate glass according to technical solution 12, wherein: g -T2 temperature range, the upper limit temperature T of the precipitation of a lithium silicate crystal phase in the substrate glass is tested. max (Li2SiO3) and the precipitation upper limit temperature of the quartz crystal phase in the matrix glass T max (SiO2), T max(Li2SiO3)≥T max (SiO2), where T g is the glass transition temperature of the substrate glass. By making the substrate glass meet the upper limit temperature Tmax (SiO2) of the precipitation of the quartz crystal phase lower than the upper limit temperature Tmax (Li2SiO3) of the precipitation of the lithium silicate crystal phase within a specific temperature range, it can be ensured that the substrate glass can effectively avoid the precipitation of the quartz crystal phase under the specific heat treatment process conditions for preparing prefabricated microcrystalline glass with petalite and lithium disilicate as the main crystal phases. Combined with the subsequent hot bending process, the lithium silicate crystal phase can also be transformed into the required lithium disilicate crystal phase, thereby avoiding the adverse effects of the quartz crystal phase and the lithium silicate crystal phase on the optical effect of the microcrystalline glass.
[0058] 14. The substrate glass according to any one of technical solutions 11 to 13, wherein the composition of the substrate glass, in terms of molar percentage of oxides, comprises:
[0059] SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: not less than 0.85mol% and less than 1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: greater than 0.00mol% and less than 1.00mol%, K2O: greater than 0.00mol% and less than 0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: greater than 0.50mol% and less than 1.50mol%, B2O3: 0.00mol%-1.00mol%. By adjusting the content relationship of the necessary oxides, it is beneficial to further improve the network structure of the glass, thereby ensuring that a large-sized prefabricated microcrystalline glass with good overall uniformity is produced, and further ensuring that a 3D curved microcrystalline glass with excellent optical properties and strength properties is produced.
[0060] 15. A method for preparing a 3D curved glass-ceramic as described in any one of technical solutions 1 to 10, comprising the following steps:
[0061] (1) heat-treating the substrate glass as described in any one of technical solutions 11 to 14 to obtain a prefabricated microcrystalline glass product containing a lithium silicate crystal phase, a lithium disilicate crystal phase and a petalite crystal phase, and having a crystallinity of not less than 60.00wt%;
[0062] (2) Processing the prefabricated microcrystalline glass product obtained in step (1) into a flat microcrystalline glass sheet of required specifications and dimensions, and heat-bending the obtained flat microcrystalline glass sheet to obtain a 3D curved microcrystalline glass, wherein the 3D curved microcrystalline glass contains a petalite crystal phase and a lithium disilicate crystal phase, and the petalite crystal phase and the lithium disilicate crystal phase have a higher weight percentage than other crystal phases present in the 3D curved microcrystalline glass.
[0063] 16. A method for preparing 3D curved microcrystalline glass according to technical solution 15, wherein in step (1), the heat treatment includes nucleation treatment and crystallization treatment, wherein the temperature of the nucleation treatment is (Tg-20°C) to (Tg+40°C), the time of the nucleation treatment is 0min-6000min, the temperature of the crystallization treatment is (T1-50°C) to T1, and the time of the crystallization treatment is 30min-6000min; Tg is the glass transition temperature of the substrate glass; in step (1), the heating rate of the heat treatment process is 5°C / min-15°C / min.
[0064] 17. The method for preparing 3D curved microcrystalline glass according to technical solution 15 or 16, wherein in step (2), the hot bending process includes at least 3 preheating stations, at least 3 hot pressing stations and at least 3 cooling stations; the temperature of the preheating station is 500℃-850℃, the temperature of the hot pressing station is 700℃-900℃, the pressure of the hot pressing station is 0MPa-1MPa, and the temperature of the cooling station is 500℃-800℃.
[0065] 18. The method for preparing 3D curved microcrystalline glass according to technical solution 17, wherein the working time of each preheating station is 90s-360s, the working time of each hot pressing station is 90s-360s, and the working time of each cooling station is 90s-360s.
[0066] 19. A chemically strengthened glass-ceramic, wherein the composition at the center of the chemically strengthened glass-ceramic is the same as the composition of the 3D curved glass-ceramic as described in any one of technical solutions 1 to 10, the chemically strengthened glass-ceramic includes a compressive stress layer region extending from the surface of the chemically strengthened glass-ceramic to the compression depth, and has tensile stress inside the chemically strengthened glass-ceramic. By forming a compressive stress layer on the surface of the 3D curved glass-ceramic, it is beneficial to further improve the mechanical properties of the 3D curved glass-ceramic.
[0067] 20. A glass device, wherein the glass device comprises the 3D curved microcrystalline glass as described in any one of Technical Solutions 1 to 10 or comprises the chemically strengthened microcrystalline glass as described in Technical Solution 19.
[0068] 21. An electronic device, wherein the electronic device comprises the 3D curved microcrystalline glass as described in any one of Technical Solutions 1-10 or comprises the chemically strengthened microcrystalline glass as described in Technical Solution 19.
[0069] One or more of the above technical solutions have at least the following advantages or
[0070] Beneficial effects:
[0071] Through the above-mentioned technical scheme, especially when the content of each oxide is within an appropriate range and in accordance with the ratio of the oxide content under specific conditions, the present application can ensure the generation of the main crystalline phase during the mass production of 3D curved microcrystalline glass products. At the same time, it can ensure that the prepared 3D curved microcrystalline glass products present a relatively uniform display effect as a whole, and effectively avoid the problem of large differences in b values in different regions of the mass-produced 3D curved microcrystalline glass products, resulting in poor display effects.
[0072] The large-sized substrate glass bricks prepared by the glass solution of the present application can ensure that the overall b value of the main surface of the prefabricated microcrystalline glass bricks is close when they are heat-treated to be prepared into prefabricated microcrystalline glass bricks, thereby ensuring that the 3D curved microcrystalline glass prepared therefrom also presents a good display effect. The scheme of the specific composition of the present application can ensure that 3D curved microcrystalline glass with good optical properties is obtained, which is conducive to the industrial mass production of 3D curved microcrystalline glass and improves the yield of 3D curved microcrystalline glass products. At the same time, the microcrystalline glass prepared by the above-mentioned substrate glass formula scheme can be prepared by chemical strengthening to obtain chemically strengthened microcrystalline glass with excellent strength properties, especially anti-drop properties.
[0073] Another technical solution or multiple technical solutions in the above technical solutions have the following advantages or beneficial effects:
[0074] In the mass production process of 3D curved glass-ceramics whose main crystal phases are petalite and lithium disilicate, products with poor optical display basically have cristobalite (SiO2) impurity phase. The present invention adjusts the composition of the substrate glass so that the substrate glass has an upper limit temperature T of quartz crystal phase precipitation within a specific temperature range. max (SiO2) is lower than the upper limit temperature T of the precipitation of lithium silicate crystal phase max (Li2SiO3) can ensure that the substrate glass can effectively avoid the precipitation of quartz crystal phase under the specific heat treatment process conditions for preparing prefabricated microcrystalline glass with main crystal phases of petalite and lithium disilicate. Combined with the subsequent hot bending process, the lithium monosilicate crystal phase can also be transformed into the required lithium disilicate crystal phase, thereby avoiding the adverse effects of the quartz crystal phase and the lithium monosilicate crystal phase on the optical effect of the glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0076] Figure 1 is a temperature-increasing DSC curve of the substrate glass of Example 1;
[0077] Figure 2 is a temperature-increasing DSC curve of the substrate glass of Example 10;
[0078] Figure 3 The DSC curve of the substrate glass of Comparative Example 1 is as follows;
[0079] Figure 4 The DSC curve of the substrate glass of Comparative Example 2 is as follows;
[0080] Figure 5 It is a schematic diagram of the structure of Li3PO4 crystals attached to lithium silicate crystals;
[0081] Figure 6 This is the standard XRD diffraction pattern of quartz in glass-ceramics;
[0082] Figure 7 A schematic diagram of nine test positions when performing b-value tests at nine locations on the main surface of a glass-ceramic;
[0083] Figure 8 The XRD diffraction pattern of the prefabricated glass-ceramics obtained after the substrate glass of Example 2 is subjected to heat treatment process C;
[0084] Fig. 9 The XRD diffraction pattern of the prefabricated glass-ceramics obtained after the substrate glass of Comparative Example 2 is subjected to heat treatment process C;
[0085] Fig.10 3D curved glass-ceramics of Example 1 have XRD diffraction curves at the maximum b value position and the minimum b value position;
[0086] Fig.11 XRD diffraction curves at the maximum b value position and the minimum b value position of the 3D curved glass-ceramics of Comparative Example 6;
[0087] Fig.12 This is a picture of the prefabricated glass-ceramics of Comparative Example 7 cracking during the 3D hot bending process;
[0088] Fig.13 This is a transmittance curve of the 3D curved microcrystalline glass of Example 1. DETAILED DESCRIPTION
[0089] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all mean that they can be included or not (or can be included or not).
[0090] Glossary and test methods:
[0091] Base glass: refers to glass that has not been nucleated, crystallized or strengthened.
[0092] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that contains both a glass phase and a crystal phase (also called a microcrystalline phase or a crystalline phase) and is prepared by targeted and controlled crystallization of the base glass.
[0093] 3D curved glass-ceramics: also known as 3D curved glass ceramics, is made by cold grinding, hot bending, hot pressing and other methods to bend the flat glass-ceramics, thereby making the two main surfaces of the flat glass-ceramics curved.
[0094] Chemically strengthened glass-ceramics: It is a solid composite material obtained after chemical strengthening treatment of glass-ceramics. During high-temperature chemical strengthening treatment, the alkali metal ions with large ionic radius (such as potassium ions and sodium ions) in the molten salt bath will replace the alkali metal ions with small ionic radius (such as sodium ions and lithium ions) in the glass-ceramics, thereby generating a volume difference of exchange ions and generating compressive stress on the surface of the glass-ceramics.
[0095] Main crystalline phase: refers to a crystalline phase having a higher weight content than other crystalline phases present in the microcrystalline glass.
[0096] Main surface: refers to the surface with the largest surface area in the glass brick or glass sheet, such as the upper and lower surfaces of the cover glass.
[0097] Flowery pieces: refers to the situation where the main surface of the glass piece shows partial coloration and / or the overall coloration of the glass piece is uneven when strong light enters the glass piece from the side. Figure 8 As shown in the figure, products with flower chips are defined as defective products during the production process because they cannot meet the display requirements of the display cover glass.
[0098] Glass transition temperature: T g , unit ℃, also known as the brittle temperature of glass, it is the highest temperature at which glass becomes brittle, and the corresponding viscosity is 10 12Pa·s, also known as the upper annealing temperature, at which the internal stress of glass products caused by uneven cooling can be eliminated. g It is obtained through the DSC curve of the substrate glass. It is manifested on the DSC curve as a step in which the baseline changes in the endothermic direction. The two baseline extension lines before and after the step are tangent to the inflection point of the curve. The average value of the corresponding temperatures of the two intersection points is the glass transition temperature.
[0099] CS_50: refers to the compressive stress value at a depth of 50μm measured from the main surface of the chemically strengthened microcrystalline glass.
[0100] DOL_0: Depth of compressive stress layer, also known as depth of compressive stress layer, refers to the distance from any surface of the glass to the position close to the surface where the compressive stress is zero in the direction of the glass thickness.
[0101] |CT_AV|: The absolute value of the average tensile stress in the tensile stress layer, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer.
[0102] Test conditions for CS_50, |CT_AV|, and DOL_0: Use SLP-2000 from Orihara, Japan, with a light source wavelength of 518nm, SOC=25.5 (nm / cm) / MPa, refractive index=1.54, and exposure time: 300usec.
[0103] When testing the surface CS_50, |CT_AV|, and DOL_0, it is necessary to first drop a conductive liquid on the stress meter, then wipe the chemically strengthened microcrystalline glass sample to be tested clean, place it on the test path, and test its stress value. The stress meter is SLP-2000 and the conductive liquid used is a conductive liquid with a refractive index of 1.51.
[0104] Transmittance: The ratio of the radiant energy that is projected and passes through an object to the total radiant energy that is projected onto the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side.
[0105] b value: belongs to the Lab color model, a color model developed by the International Illumination Commission. Positive and negative b values represent yellow and blue.
[0106] Haze: Haze is the percentage of transmitted light intensity that deviates from the incident light by more than 2.5° to the total transmitted light intensity.
[0107] Precursor: A form of existence before obtaining the target object.
[0108] Residual glass phase: refers to the amorphous phase in microcrystalline glass.
[0109] Synchronous thermal analysis test: Use Mettler Toledo TGA / DSC3+ synchronous thermal analyzer to test according to the required process. The obtained curve is called DSC curve, including heating DSC curve.
[0110] Test conditions for the temperature-increasing DSC curve: After grinding the substrate glass, sieve through 200 mesh to obtain the sample to be tested, weigh about 20 mg of the sample, and heat it from room temperature to 900°C at a heating rate of 10°C / min under a nitrogen atmosphere to obtain the temperature-increasing DSC curve of the sample. The differential thermal analysis instrument used in this application to test the temperature-increasing DSC curve is a Mettler-Toledo TGA / DSC3+ synchronous thermal analyzer, the standard used in the test is α-Al2O3 powder, the container for placing the sample is a platinum crucible, the ambient temperature of the instrument is 24°C, and the air humidity is 40%.
[0111] Glass thickness: measured by laser thickness gauge.
[0112] Optical performance test of microcrystalline glass with a thickness of less than 2 mm: This application uses the transmission mode of Konica Minolta's CM-3600A spectrophotometer to test the haze, L, a, and b values of microcrystalline glass. The test aperture of the CM-3600A spectrophotometer used is 25.6 mm. This application uses Shimadzu's UV-2000 ultraviolet visible spectrophotometer to test the transmittance and its curve. To ensure accuracy, this test method is suitable for testing glass sheets with a thickness of less than 2 mm.
[0113] Determination of crystal phase: The XRD test results (RAW format) are imported into the X-ray diffraction data Rietveld refinement software JADE Standard 8.6 for fitting and analysis to determine the crystal phase in the microcrystalline glass sample.
[0114] The crystal content in this application refers to the percentage of crystals or crystalline phases in the mass of microcrystalline glass, which is a weight percentage.
[0115] Determination of crystal content: Import the XRD test results (RAW format) into the X-ray diffraction data Rietveld refinement software JADE Standard 8.6 for fitting and calculation to obtain the crystal content in the microcrystalline glass sample. Specifically, the ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content.
[0116] Average crystal size test: The average crystal size of the sample can be calculated according to the Scherrer formula D = Kλ / (βcosθ) using the result data obtained from the XRD test. Wherein, λ is the X-ray wavelength, λ = 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction spectrum) output by the XRD instrument is curve-fitted in the JADE Standard 8.6 software, and Jade outputs the fitting report. According to the angle 2θ value and Peak FWHM value (half-height width of the diffraction peak) corresponding to each diffraction peak in the fitting report, the Peak FWHM value is converted into the radian system: β = (FWHM / 180×3.14), and the grain size of each diffraction peak is calculated by the Scherrer formula D = Kλ / (βcosθ) and then averaged to obtain the average crystal size.
[0117] The test method of the upper limit temperature of crystal phase precipitation is as follows: the substrate glass is heated at a heating rate of 10°C / min, and the substrate glass is heated to Tg, Tg+5°C, Tg+10°C, Tg+15°C respectively, and the heat treatment is continued at an increase of 5°C until T2, and the heat treatment time at each temperature is 30-240min (the corresponding heat treatment time at each temperature in the embodiments and comparative examples of the present application is 240min). The crystal phase composition of the samples obtained by treating the substrate glass under the above-mentioned different heat treatment temperature conditions is tested to obtain the upper limit temperature of precipitation of a lithium silicate (Li2SiO3) crystal phase and a quartz (SiO2) crystal phase.
[0118] Here, the "upper limit temperature of the precipitation of lithium silicate crystal phase" specifically refers to the temperature at which g -T2 temperature range is the highest temperature at which a lithium silicate crystal phase is precipitated in the substrate glass. Above this temperature, lithium silicate will not precipitate in the substrate glass.
[0119] The "upper limit temperature of the quartz crystal phase precipitation" here specifically refers to the temperature at which g -T2 is the highest temperature at which quartz crystal phase is precipitated in the substrate glass. If the temperature exceeds this temperature, quartz will not precipitate in the substrate glass. The standard XRD diffraction pattern of quartz in microcrystalline glass is as follows: Figure 6 shown.
[0120] Here is the T g T2 is the second exothermic peak temperature in the heating DSC curve obtained when the substrate glass is subjected to DSC test.
[0121] If a certain crystal phase always exists at the temperature point T2, it means that its upper precipitation temperature is greater than T2.
[0122] Fixed height drop test:
[0123] (1) Stick 120-grit sandpaper on the bottom surface of the 187g model machine and place the model machine on the Wonder Inno drop test machine;
[0124] (2) Place a glass-ceramic sample to be tested with a length, width and thickness of 50 mm × 50 mm × 0.6 mm on a smooth marble plate directly below the model machine, with the glass-ceramic sample facing the sandpaper;
[0125] (3) Drop the model machine from a fixed height of 1.0 m to impact the glass-ceramic sample directly below the model machine. If the glass-ceramic sample is not broken, replace the sandpaper on the lower surface of the model machine and repeat the above drop impact process until the glass-ceramic breaks, and record the number of drops when it breaks.
[0126] At least 10 identical glass-ceramic samples are taken from each batch for a fixed-point height drop test, and the average value of the test results of the 10 glass-ceramic samples is calculated to characterize the drop resistance of the glass-ceramic.
[0127] Surface Na2O concentration test: Surface Na2O concentration is equal to surface Na2O mass / total surface oxide mass, where the total surface oxide mass includes oxides such as SiO2, Al2O3, P2O5, ZrO2, Na2O, K2O, CaO that can be accurately tested by XRF, but does not include the content of oxides such as Li2O and B2O3 that cannot be accurately tested by XRF. The surface Na2O concentration of the chemically strengthened microcrystalline glass in this application was measured by X-ray fluorescence spectrometer (XRF), and the test equipment used was Thermo ScientificARL TM PERFORM'X. The target material is Rh (rhodium), the light tube voltage is 40KW, the current is 60mA, the collimator is 0.15, the crystal is LiF200, the detector is FPC, the test range is 29mm circle, and the analysis software is UniQuant standardless analysis. Standardless testing is used during XRF testing, and the concentration of elements or their oxides with atomic numbers 6 and below in the glass is not tested. That is, in this application, when the surface Na2O concentration is tested by XRF, the total mass of the surface oxide does not include the mass of elements or their oxides with atomic numbers 6 and below in the glass.
[0128] As described above, the present application provides a 3D curved glass-ceramic, wherein the 3D curved glass-ceramic contains petalite (LiAlSi4O 10 ) crystalline phase and lithium disilicate (Li2Si2O5) crystalline phase, wherein the petalite crystalline phase and the lithium disilicate crystalline phase have a higher weight percentage than other crystalline phases present in the 3D curved microcrystalline glass.
[0129] The 3D curved microcrystalline glass of the present application is obtained by subjecting the substrate glass to heat treatment and heat bending treatment. Therefore, it can be understood that, in terms of oxides, the composition of the substrate glass is the same as that of the 3D curved microcrystalline glass.
[0130] In the present application, the composition of the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics includes, in terms of molar percentage of oxides:
[0131] SiO2: 60.00mol%-71.00mol%, Al2O3: 1.50mol%-5.00mol%, P2O5: 0.80mol%-1.50mol%, ZrO2: 2.00mol%-4.00mol%, Na2O: 0.00m ol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-30.00mol%, CaO: 0.00mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%;
[0132] In terms of the content expressed by the molar percentage of each oxide in the composition of the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic, the composition of the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic satisfies:
[0133] 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250;
[0134] 18.200≤Li2O / P2O5≤25.500;
[0135] 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.200;
[0136] 1.500≤10×(ZrO2+P2O5) / Li2O≤2.000;
[0137] 4.000≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤6.000;
[0138] 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤5.000;
[0139] 12.200≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.000. When the content of each oxide is within an appropriate range and the content ratio of the oxide is matched under specific conditions, the generation of the main crystalline phase can be ensured in the process of mass production of 3D curved glass-ceramics products. At the same time, the prepared 3D curved glass-ceramics products can be ensured to present a relatively uniform display effect as a whole, effectively avoiding the problem of large differences in b values in different regions of mass-produced 3D curved glass-ceramics products and poor display effects.
[0140] In the glass system of the present application, SiO2 is an oxide that forms a glass network skeleton, which is used to stabilize the network structure of the substrate glass and the 3D curved microcrystalline glass, and is an important component of the crystal phases such as lithium silicate, petalite, β-spodumene and quartz. When the substrate glass is heat-treated to form microcrystalline glass, the content of SiO2 should be high enough to form a sufficient amount of petalite crystals and lithium silicate crystals. When the SiO2 content is too little, the glass has a tendency to increase its thermal expansion coefficient and reduce its thermal shock resistance; when the SiO2 content is too much, the glass will have a poor solubility, or the viscosity of the molten glass liquid will increase, making the glass liquid difficult to clarify, making the glass molding more difficult, reducing productivity, and also causing the crystallization heat treatment time of the substrate glass to be prolonged. In some embodiments, the microcrystalline glass or substrate glass of the present application contains 60.00mol%-71.00mol% SiO2. In some embodiments, the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics may contain 60.00mol%-71.00mol%, 60.90mol%-70.00mol%, 60.90mol%-69.00mol%, 60.90mol%-68.00mol%, 62.00mol%-65.00mol%, 63.00mol%-70.00mol%, 64.00mol%-68.00mol%, 65.00mol%-67.00mol% or 67.50mol%-71.00mol% SiO2. In some embodiments, the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic may contain 60.00mol%, 61.00mol%, 62.00mol%, 63.00mol%, 64.00mol%, 65.00mol%, 66.00mol%, 67.00mol%, 67.50mol%, 68.00mol%, 69.00mol%, 70.00mol% or 71.00mol% of SiO2, or SiO2 within the numerical range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramic or substrate glass with the performance required by the present application can be obtained.
[0141] In the glass system of the present application, Al2O3 can be used to construct the glass skeleton and is an indispensable component for forming petalite. Al2O3 is coordinated around the crystal nucleus to form a "center-shell" structure. This structure makes it difficult for the crystal nucleus components to be supplied from the outer part of the shell, and the crystal nucleus is not easy to grow, and it is easy to form multiple tiny grains. An appropriate amount of Al2O3 can stabilize the glass network structure, improve mechanical properties and chemical durability, and inhibit the phase separation of the glass, reduce the thermal expansion coefficient, and increase the strain point. When the Al2O3 content is too little, the glass has a tendency to increase the thermal expansion coefficient, its chemical durability is reduced, and the crystal nucleus becomes larger, and the microcrystalline glass is prone to white turbidity; when the Al2O3 content is too much, the glass has a poor meltability, production becomes difficult, and mullite crystals are easily precipitated to make the glass devitrified. In some embodiments, the 3D curved microcrystalline glass of the present application or the substrate glass for preparing the 3D curved microcrystalline glass contains 1.50mol%-5.00mol%. In some embodiments, the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic may contain 1.50mol%-5.00mol%, 3.00mol%-5.00mol%, 3.00mol%-4.00mol%, 3.00mol%-4.50mol%, 3.50mol%-4.50mol% or 4.50mol%-5.00mol% of Al2O3. In some embodiments, the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic may contain 1.50mol%, 2.00mol%, 2.50mol%, 3.00mol%, 3.20mol%, 3.80mol%, 4.00mol%, 4.40mol%, 4.80mol% or 5.00mol% of Al2O3, or Al2O3 within the numerical range formed by any two of the above specific numerical values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as a 3D curved microcrystalline glass or substrate glass with the performance required by the present application can be obtained.
[0142] In the glass system of the present application, Li2O is the main component of the petalite crystal phase and the lithium silicate crystal phase, and is also a necessary component for chemical strengthening. An appropriate amount of Li2O is conducive to ensuring that the transparency, melt forming effect, crystallization ability, chemical strengthening performance and other properties of the 3D curved glass-ceramics meet the requirements. When the Li2O content is too little, the glass is prone to precipitate crystalline phases, such as mullite, which makes the glass devitrified, the meltability is reduced or the viscosity is increased, it is difficult to clarify, and the molding becomes difficult; when the Li2O content is too much, the crystallization heat treatment temperature of the substrate glass is reduced, the crystallization ability of the glass becomes too strong, the glass has a tendency to devitrify, and the crystallized glass becomes easily broken. In some embodiments, the 3D curved glass-ceramics of the present application or the substrate glass for preparing the 3D curved glass-ceramics contains 20.00mol%-30.00mol% Li2O. In some embodiments, the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics may contain 20.00mol%-30.00mol%, 22.00mol%-28.00mol%, 24.00mol%-26.00mol%, 20.00mol%-24.00mol%, 24.00mol%-30.00mol%, 20.00mol%-22.00mol%, 28.00mol%-30.00mol% or 21.00mol%-28.00mol% of Li2O. In some embodiments, the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics may contain 20.50mol%, 21.50mol%, 22.50mol%, 23.50mol%, 24.50mol%, 25.50mol%, 26.50mol%, 27.50mol%, 28.50mol%, 29.50mol% or 30.00mol% of Li2O, or Li2O within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramics or substrate glass with the performance required by the present application can be obtained.
[0143] In the glass system of the present application, P2O5 is a glass-forming oxide, which exists in the network structure as phosphorus-oxygen tetrahedron [PO4]. P2O5 appears preferentially during the heat treatment process, first causing the glass to phase separate and aggregate to form an amorphous precursor phase Li3PO4, and then using Li3PO4 as a non-uniform nucleation point, crystalline phases such as lithium silicate grow attached to the amorphous Li3PO4. As the P2O5 content increases, the number of non-uniform nucleation points increases, and the grains with Li3PO4 as the nucleation point are effectively refined, which is beneficial to improving the overall transmittance of the microcrystalline glass, the uniformity of the glass, and reducing the b value. Within a certain range of P2O5, the gain effect is optimal. However, when the P2O5 content is too high, the crystallization upper limit temperature rises, and more Li3PO4 crystals are easily generated, resulting in insufficient Li2O content for forming lithium silicate and petalite, which in turn causes the substrate glass to easily precipitate quartz crystals, resulting in a decrease in the transmittance of the microcrystalline glass and the overall optical uniformity of the microcrystalline glass. Worse still, the substrate glass is directly crystallized during melting and forming. When the P2O5 content is too low, coarse ZrO2 crystals are easily precipitated, causing the glass to lose transparency.
[0144] In some embodiments, the 3D curved glass-ceramic of the present application or the substrate glass for preparing the 3D curved glass-ceramic contains 0.80mol%-1.50mol% P2O5. The P2O5 in this content range is conducive to ensuring that the 3D curved glass-ceramic has high transmittance, good optical uniformity, significantly reduces the b value, and achieves the best gain effect. In some embodiments, the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic can contain 0.80mol%-1.50mol%, 0.80mol%-1.30mol%, 1.30mol%-1.50mol%, 0.80mol%-1.00mol%, 1.00mol%-1.30mol% or 1.10mol%-1.50mol% P2O5. In some embodiments, the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic may contain 0.85 mol%, 0.95 mol%, 1.00 mol%, 1.10 mol%, 1.20 mol%, 1.35 mol%, 1.40 mol% or 1.50 mol% of P2O5, or P2O5 within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramic or substrate glass with the performance required by the present application can be obtained.
[0145] In the glass system of the present application, since P2O5 preferentially generates amorphous Li3PO4 during heat treatment, the increase of P2O5 will inevitably compete for more Li2O, thereby reducing the production of lithium silicate and petalite, so a certain degree of Li2O needs to be supplemented. In this regard, in the system of the present application, the composition of the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics is expressed in terms of the molar percentage of each oxide in the composition, and the composition of the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics satisfies: 18.200≤Li2O / P2O5≤25.500, where the chemical formula represents the molar percentage of the oxide, which is beneficial to ensure the generation of the main crystalline phase and improve the strength performance of the glass. In some embodiments, the value of Li2O / P2O5 can be, for example, 18.200, 18.500, 19.000, 19.500, 20.000, 20.500, 21.000, 21.500, 22.000, 22.500, 23.000, 23.500, 24.000, 24.500, 25.000 or 25.500, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0146] In some embodiments, the composition of the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics, expressed as the content of each oxide in the molar percentage, satisfies: 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250, where the chemical formula represents the molar percentage of the oxide, thereby facilitating the formation of petalite and lithium disilicate main crystalline phases. In some embodiments, the value of 5×P2O5 / (Li2O+0.5Al2O3) can be, for example, 0.180, 0.184, 0.190, 0.200, 0.210, 0.220, 0.230, 0.240, 0.245 or 0.250, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0147] In some embodiments, the composition of the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic satisfies the following conditions: 4.000≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤6.000, where the chemical formula represents the molar percentage of the oxide, which is beneficial for ensuring the optical properties of the 3D curved glass-ceramic. In some embodiments, the value of (SiO2-7Al2O3-Li2O) / (P2O5+ZrO2) can be, for example, 4.000, 4.200, 4.500, 5.000, 5.500 or 6.000, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0148] In the glass system of the present application, an appropriate amount of ZrO2 can improve the viscosity, hardness, elastic modulus, refractive index, chemical stability of the glass and reduce the thermal expansion coefficient of the glass. ZrO2 does not play the role of a nucleating agent in the microcrystalline glass with petalite and lithium silicate structure. ZrO2 exists in the residual glass phase after heat treatment, which effectively improves the mechanical properties of the residual glass phase. However, excessive ZrO2 will increase the difficulty of melting the substrate glass, and white zirconium precipitate will be produced during discharge, which is not conducive to the production of transparent microcrystalline glass. In some embodiments, the 3D curved microcrystalline glass of the present application or the substrate glass for preparing the 3D curved microcrystalline glass contains 2.00mol%-4.00mol% ZrO2. ZrO2 that meets this content range is conducive to the production of transparent 3D curved microcrystalline glass and is conducive to improving the mechanical properties of 3D curved microcrystalline glass. In some embodiments, the 3D curved glass-ceramics or the base glass for preparing the 3D curved glass-ceramics may contain 2.00mol%-4.00mol%, 2.50mol%-3.50mol%, 2.70mol%-3.30mol%, 2.90mol%-3.10mol%, 2.50mol%-3.00mol%, 2.50mol%-2.80mol%, 2.80mol%-3.50mol%, 2.80mol%-3.40mol%, 2.80mol%-3.30mol% or 2.80mol%-3.10mol% ZrO2. In some embodiments, the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic may contain 2.00mol%, 2.50mol%, 2.75mol%, 2.95mol%, 3.15mol%, 3.25mol%, 3.35mol%, 3.50mol% or 4.00mol% ZrO2, or ZrO2 within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramic or substrate glass with the performance required by the present application can be obtained.
[0149] In some embodiments, the composition of the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic satisfies the following conditions: 1.500≤10×(ZrO2+P2O5) / Li2O≤2.000, where the chemical formula represents the molar percentage of the oxide, which is conducive to ensuring the strength performance of the 3D curved glass-ceramic. In some embodiments, the value of 10×(ZrO2+P2O5) / Li2O can be, for example, 1.500, 1.550, 1.600, 1.700, 1.800, 1.900, 1.95 or 2.000, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0150] In the glass system of the present application, B2O3 helps to lower the melting temperature of the substrate glass. B2O3 has boron-oxygen triangles [BO3] and boron-oxygen tetrahedrons [BO4] as structural units. As the content of B2O3 increases, the relative content of boron-oxygen triangles and boron-oxygen tetrahedrons changes, resulting in a reversal of structure and properties. An appropriate amount of B2O3 helps to lower the melting temperature of the substrate glass and improve the transmittance, overall uniformity and other properties of the 3D curved microcrystalline glass. However, when too much B2O3 is added, on the one hand, the three-dimensional framework structure of the boron-oxygen tetrahedron [BO4] is transformed into a two-dimensional layered structure of the boron-oxygen triangle [BO3], and the three-coordinated boron-oxygen triangle [BO3] is not as strong as the boron-oxygen tetrahedron [BO4], which will have the effect of opening the network structure. At the same time, the increase in the B2O3 content in the residual glass phase will reduce the viscosity of the residual glass phase and promote the growth of crystals such as lithium silicate; on the other hand, it will reduce the temperature of the second exothermic peak of the DSC curve of the substrate glass, increase the precipitation of SiO2 crystal phase (such as quartz), affect the glass transmittance, and also make the overall uniformity of the glass brick worse. In some embodiments, the 3D curved microcrystalline glass of the present application or the substrate glass for preparing the 3D curved microcrystalline glass contains 0.00mol%-1.00mol%. In some embodiments, the glass-ceramics or the substrate glass may contain 0.00mol%-1.00mol%, 0.10mol%-0.90mol%, 0.30mol%-0.80mol%, 0.50mol%-0.70mol%, 0.00mol%-0.60mol%, 0.00mol%-0.50mol%, 0.60mol%-1.00mol%, 0.50mol%-1.00mol% or 0.30mol%-0.50mol% B2O3. In some embodiments, the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics may contain 0.00 mol%, 0.15 mol%, 0.25 mol%, 0.35 mol%, 0.45 mol%, 0.55 mol%, 0.75 mol%, 0.95 mol% or 1.00 mol% B2O3, or B2O3 within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramics or substrate glass with the performance required by the present application can be obtained.
[0151] In the glass system of the present application, Na2O is an oxide outside the glass network, which can provide free oxygen to increase the oxygen-silicon ratio in the glass structure, and play a role in adjusting the grain size; the presence of an appropriate amount of Na2O is conducive to promoting the precipitation of lithium disilicate crystal phase, reducing the crystallization tendency of glass, and increasing the transmittance of glass. At the same time, it is conducive to improving the thermal stability, chemical stability, mechanical strength and weather resistance of glass. In some embodiments, the 3D curved microcrystalline glass of the present application or the substrate glass for preparing the 3D curved microcrystalline glass contains 0.00mol%-1.00mol% Na2O. In some embodiments, the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics may contain 0.00mol%-1.00mol%, 0.20mol%-0.90mol%, 0.40mol%-0.80mol%, 0.00mol%-0.40mol%, 0.00mol%-0.50mol%, 0.00mol%-0.40mol%, 0.40mol%-1.00mol%, 0.30mol%-0.50mol% or 0.40mol%-0.60mol% of Na2O. In some embodiments, the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic may contain 0.00 mol%, 0.15 mol%, 0.35 mol%, 0.55 mol%, 0.75 mol%, 0.95 mol% or 1.00 mol% of Na2O, or Na2O within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramic or substrate glass with the performance required by the present application can be obtained.
[0152] In the glass system of the present application, K2O is an oxide outside the glass network. An appropriate amount of K2O can reduce the tendency of glass to crystallize and increase the transparency and gloss of the glass. However, when the K2O content is too high, the crystallization ability of the glass becomes stronger, the glass is prone to devitrification, and the crystallized glass is prone to breakage. + The ionic radius is larger than that of Li + , it is not easy to enter the crystal, so the K +Remains in the glass phase. Therefore, in some embodiments, the 3D curved glass-ceramics of the present application or the substrate glass for preparing the 3D curved glass-ceramics contains 0.00mol%-0.50mol%. In some embodiments, the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics may contain 0.00mol%-0.50mol%, 0.10mol%-0.40mol%, 0.20mol%-0.30mol%, 0.00mol%-0.20mol%, 0.30mol%-0.50mol%, 0.10mol%-0.20mol% or 0.20mol%-0.40mol% K2O. In some embodiments, the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic may contain 0.00 mol%, 0.15 mol%, 0.25 mol%, 0.35 mol%, 0.45 mol% or 0.50 mol% of K2O, or K2O within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramic or substrate glass with the performance required by the present application can be obtained.
[0153] In the glass system of the present application, CaO is beneficial to increase the chemical stability and mechanical strength of the glass. CaO reduces the viscosity of the glass, enhances the solubility and formability of the glass, and is also beneficial to adjust the thermal expansion coefficient and refractive index of the microcrystalline glass. However, when the CaO content is too high, the glass is prone to devitrification after crystallization. Excessive CaO residues in the glass phase produce a refractive index difference with the main crystal phase, which will cause the transmittance of the microcrystalline glass to decrease and the haze to increase. In some embodiments, the 3D curved microcrystalline glass of the present application or the substrate glass for preparing the 3D curved microcrystalline glass contains 0.00 mol%-1.60 mol% CaO. In some embodiments, the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics may contain 0.00mol%-1.60mol%, 0.50mol%-1.60mol%, 0.60mol%-1.50mol%, 0.80mol%-1.30mol%, 1.00mol%-1.20mol%, 0.50mol%-1.00mol%, 0.50mol%-0.85mol%, 0.85mol%-1.40mol%, 1.40mol%-1.60mol%, 0.85mol%-1.20mol%, 1.20mol%-1.60mol%, 0.85mol%-1.00mol%, 0.85mol%-0.90mol% or 1.00mol%-1.30mol% CaO. In some embodiments, the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic may contain 0.00mol%, 0.50mol%, 0.70mol%, 0.85mol%, 1.10mol%, 1.25mol%, 1.35mol%, 1.45mol% or 1.60mol% CaO, or CaO within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramic or substrate glass with the performance required by the present application can be obtained.
[0154] In some embodiments, based on the content expressed by the molar percentage of each oxide in the composition of the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics, the composition of the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics satisfies: 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.200, where the chemical formula represents the molar percentage of the oxide, thereby facilitating the formation of 3D curved glass-ceramics that meet specific structures and have excellent performance (especially the molding performance, optical performance and strength performance of the 3D curved glass-ceramics). In some embodiments, the value of P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3) can be, for example, 0.100, 0.150, 0.190, 0.200, 0.205, 0.210, 0.250, 0.300, 0.350, 0.380, 0.400, 0.600, 0.800, 1.000, 1.200, 1.400, 1.600, 1.800, 2.000 or 2.200, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0155] In some embodiments, the composition of the 3D curved glass-ceramic or the substrate glass for preparing the 3D curved glass-ceramic satisfies the following conditions: 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000×K2O)≤5.000, where the chemical formula represents the molar percentage of the oxide, which is conducive to forming a 3D curved glass-ceramic that satisfies a specific structure and has excellent performance (especially the strength performance of the 3D curved glass-ceramic). In some embodiments, the value of 99×(CaO+ZrO2) / (Li2O+Na2O+1000×K2O) can be 2.600, 2.800, 3.000, 3.500, 4.000 or 5.000, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0156] In some embodiments, based on the content expressed by the molar percentage of each oxide in the composition of the 3D curved glass-ceramic or the base glass for preparing the 3D curved glass-ceramic, the composition of the 3D curved glass-ceramic or the base glass for preparing the 3D curved glass-ceramic satisfies: 12.200≤(5.6×B2O3+10×Al2O3+6.5×CaO) / ZrO2≤20.000, where the chemical formula represents the molar percentage of the oxide, thereby facilitating the formation of 3D curved glass-ceramic that meets a specific structure and has excellent performance (especially the optical properties and mechanical properties of the 3D curved glass-ceramic). In some embodiments, the value of (5.6×B2O3+10×Al2O3+6.5×CaO) / ZrO2 can be 12.200, 13.000, 14.000, 15.000, 16.000, 17.000, 18.000, 19.000 or 20.000, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0157] In some embodiments, the 3D curved glass-ceramics is transparent in the visible light range, where visible light refers to light in the wavelength range of 360nm-780nm, and "transparent in the visible light range" means that the transmittance under the light in the wavelength range of 360nm-780nm is greater than 80%, which can meet the optical performance requirements of the front cover display effect. In some embodiments, the transmittance of the 0.6mm thick 3D curved glass-ceramics in the visible light range is not less than 90%.
[0158] In some embodiments, the composition of the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics, measured in molar percentage of oxides, includes: SiO2: 67.50 mol%-71.00 mol%, Al2O3: 3.50 mol%-5.00 mol%, P2O5: not less than 0.85 mol% and less than 1.50 mol%, ZrO2: 2.50 mol%-3.50 mol%, Na2O: greater than 0.00 mol% and not more than 1.00 mol%, K2O: greater than 0.00 mol% and not more than 0.50 mol%, Li2O: 20.00 mol%-25.00 mol%, CaO: greater than 0.50 mol% and not more than 1.50 mol%, B2O3: 0.00 mol%-1.00 mol%.
[0159] In some embodiments, the 3D curved glass-ceramics does not contain a quartz crystal phase. The standard XRD diffraction pattern of quartz in the glass-ceramics is as follows: Figure 6As shown. In the microcrystalline glass whose main crystal phase is petalite crystal phase and lithium disilicate crystal phase, if quartz crystal phase is precipitated, it will have an adverse effect on the optical properties of the microcrystalline glass, easily leading to a decrease in the transmittance of the microcrystalline glass, and also easily making the overall uniformity of the microcrystalline glass brick worse, and then there will be a problem of large differences in b-values in different areas of the glass. The ratio of each oxide in the present application can enable the base glass to mass-produce 3D curved microcrystalline glass without quartz crystal phase under specific heat treatment process conditions.
[0160] In some embodiments, in the 3D curved glass-ceramics, the total content of the petalite crystalline phase and the lithium disilicate crystalline phase accounts for more than 60.00wt% of the mass of the 3D curved glass-ceramics, preferably more than 70.00wt%, and more preferably more than 80.00wt%. A higher content of the petalite crystalline phase and the lithium disilicate crystalline phase is beneficial to improving the mechanical strength of the 3D curved glass-ceramics. The total content of the petalite crystalline phase and the lithium disilicate crystalline phase accounts for the weight percentage of the mass of the glass-ceramics, for example, 60.00wt%, 65.00wt%, 68.00wt%, 70.00wt%, 75.00wt%, 80.00wt%, 85.00wt%, 90.00wt%, 93.00wt%, 95.00wt%, 98.00wt% or 100.00wt%, or a crystallinity within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as a 3D curved glass-ceramic with the performance required by the present application can be obtained.
[0161] In some embodiments, in the 3D curved glass-ceramics, the petalite crystalline phase accounts for 35.00wt%-50.00wt% of the mass of the transparent glass-ceramics, and the lithium disilicate crystalline phase accounts for 35.00wt%-50.00wt% of the mass of the transparent glass-ceramics. In some embodiments, the percentage of the lithium disilicate crystalline phase or the petalite crystalline phase in the mass of the transparent glass-ceramics can be 35.00wt%-50.00wt%, 35.00wt%-45.00wt%, 35.00wt%-40.00wt% or 40.00wt%-50.00wt%. In some embodiments, the glass-ceramics may contain 35.00wt%, 40.00wt%, 45.00wt% or 50.00wt% of the lithium disilicate crystalline phase or the petalite crystalline phase, or the lithium disilicate crystalline phase or the petalite crystalline phase within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the microcrystalline glass with the required performance of the present application can be obtained.
[0162] In some embodiments, the glass-ceramics contains one or more of a lithium silicate (Li2SiO3) crystal phase, a lithium phosphate (Li3PO4) crystal phase, and a spodumene crystal phase as secondary crystalline phases. In some embodiments, in the glass-ceramics, the secondary crystalline phase accounts for less than 20.00wt% of the mass of the transparent glass-ceramics. The glass-ceramics of the present application have a low secondary crystalline phase content, which is more conducive to ensuring a high content of the main crystalline phase, and thus ensuring the excellent mechanical strength properties of the glass-ceramics. In some embodiments, the lithium phosphate (Li3PO4) crystal phase is usually accompanied by the growth of secondary phases such as a lithium silicate (Li2SiO3) crystal phase, such as Figure 5 shown.
[0163] In some embodiments, in the transparent glass-ceramics, a lithium silicate crystal phase accounts for less than 8.00 wt% of the mass of the transparent glass-ceramics, and a total amount of a lithium phosphate crystal phase and a spodumene crystal phase accounts for less than 8.00 wt% of the mass of the transparent glass-ceramics.
[0164] In some embodiments, in the 3D curved glass-ceramics, the average crystal size does not exceed 100 nm, for example, it can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, or the average crystal size within the numerical range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent 3D curved glass-ceramics with the performance required by the present application can be obtained.
[0165] In some embodiments, the crystallinity of the 3D curved glass-ceramics is ≥70.00wt%, preferably ≥80.00wt%, which is beneficial to improving the mechanical strength performance of the glass-ceramics. The "crystallinity" here refers to the percentage of the content of all crystalline phases / crystals in the 3D curved glass-ceramics to the mass of the 3D curved glass-ceramics, for example, it can be 70.00wt%, 80.00wt%, 85.00wt%, 90.00wt%, 93.00wt%, 95.00wt%, 98.00wt% or 100.00wt%, or a crystallinity within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramics with the performance required by the present application can be obtained.
[0166] In some embodiments, when the thickness is 0.6 mm, the optical b value of the 3D curved glass-ceramics is ≤1.00, preferably the optical b value is ≤0.70, and more preferably the optical b value is ≤0.55. In some embodiments, the optical b value of the 3D curved glass-ceramics at this thickness can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90 or 1.00, or a value within the numerical range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the 3D curved glass-ceramics with the performance required by the present application can be obtained.
[0167] Among them, the locations of nine are as follows Figure 7 As shown in the figure, they are: (1) four test positions of test circle I near the four corners of the main surface; (2) four test positions of test circle II formed by the point closest to the middle of the long side or short side of the main surface on the line segment formed by the centers of the four test circles I, a total of four test positions; (3) one test circle III formed by the center point of the main surface. The diameter of the test circle depends on the size of the instrument's test window (which is a circle).
[0168] In some embodiments, when the thickness is 0.6 mm, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics is ≤0.30, preferably the range of the b values at nine locations on the main surface is ≤0.10, and more preferably the range of the b values at nine locations on the main surface is ≤0.06. In some embodiments, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics at this thickness may be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.20, 0.25 or 0.30, or a range within the numerical range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the 3D curved glass-ceramics with the performance required by the present application can be obtained.
[0169] In some embodiments, when the thickness of the 3D curved glass-ceramics is 0.6 mm, the haze is ≤0.20%, and the transmittance of the glass-ceramics is ≥90.00% under 550 nm wavelength light. The b value here refers to the b value at any position of the glass-ceramics. In some embodiments, the transmittance of 550 nm wavelength light of 0.6 mm thick glass-ceramics can be 90.00%, 90.50%, 91.00%, 92.00%, 93.00%, 94.00%, 95.00%, 96.00%, 97.00%, 98.00%, 99.00%, 100.00%, or a transmittance within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics with the performance required by the present application can be obtained.
[0170] As described above, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics mass-produced in the present application is small, that is, the b values of different areas of the 3D curved glass-ceramics are close; and the 3D curved glass-ceramics in the present application has high transmittance, low b value, and low haze, which indicates that the 3D curved glass-ceramics mass-produced by the production line in the present application has better optical properties and good display uniformity, and can meet the application requirements of display cover plates.
[0171] The present application also provides a substrate glass, which can be used to prepare the 3D curved microcrystalline glass mentioned above, wherein the composition of the substrate glass is the same as that of the aforementioned 3D curved microcrystalline glass in terms of molar percentage of oxides.
[0172] In some embodiments, through simultaneous thermal analysis testing, under a nitrogen protective atmosphere, the substrate glass is heated from room temperature to 900°C at a heating rate of 10°C / min to obtain a heating DSC curve, in which there are at least two exothermic peaks, wherein the first exothermic peak temperature T1 is 600°C-730°C, and the second exothermic peak temperature T2 is 740°C-800°C, and T1 and T2 satisfy the relationship: 100°C ≥ T2-T1 ≥ 40°C, preferably 80°C ≥ T2-T1 ≥ 50°C.
[0173] In some embodiments, at T g -T2 temperature range, the upper limit temperature T of the precipitation of a lithium silicate crystal phase in the substrate glass is tested. max (Li2SiO3) and the precipitation upper limit temperature of the quartz crystal phase in the matrix glass T max (SiO2), T max (Li2SiO3)≥T max (SiO2), where T gis the glass transition temperature of the substrate glass. T2 here is the second exothermic peak temperature in the above-mentioned temperature-increasing DSC curve.
[0174] Large-sized substrate glass bricks made of a specific substrate glass solution that meets specific thermal properties can be heat-treated under the production line process conditions for mass production of 3D curved micro-ceramics to obtain prefabricated micro-ceramics bricks with uniform b value distribution. The flat micro-ceramics products made by slicing the prefabricated micro-ceramics bricks can be heat-bent to obtain 3D curved micro-ceramics with better display effects. Moreover, by making the substrate glass meet the upper limit temperature Tmax (SiO2) of the precipitation of the quartz crystal phase lower than the upper limit temperature Tmax (Li2SiO3) of the precipitation of the lithium silicate crystal phase within a specific temperature range, it can ensure that the substrate glass effectively avoids the precipitation of the quartz crystal phase under the specific heat treatment process conditions for preparing prefabricated micro-ceramics with the main crystal phases of petalite and lithium disilicate. Combined with the subsequent heat bending process, the lithium silicate crystal phase can also be transformed into the desired lithium disilicate crystal phase, thereby avoiding the adverse effects of the quartz crystal phase and the lithium silicate crystal phase on the optical effect of the micro-ceramics.
[0175] Before preparing large-sized prefabricated microcrystalline glass bricks, a small sample of the base glass can be made according to the glass formula. By obtaining the above-mentioned characteristics, it can be verified whether the glass solution is suitable for mass production of qualified 3D curved microcrystalline glass products on the production line. If it does not meet the requirements, adjustments can be made in time, which can greatly save time and cost and effectively avoid waste of resources.
[0176] In some embodiments, the composition of the 3D curved glass-ceramics or the substrate glass for preparing the 3D curved glass-ceramics includes, in terms of molar percentage of oxides:
[0177] SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: not less than 0.85mol% and less than 1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: greater than 0.00mol% and less than 1.00mol%, K2O: greater than 0.00mol% and less than 0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: greater than 0.50mol% and less than 1.50mol%, B2O3: 0.00mol%-1.00mol%;
[0178] In terms of the content expressed by the molar percentage of each oxide in the composition of the 3D curved glass-ceramics or the base glass for preparing the 3D curved glass-ceramics, the composition of the 3D curved glass-ceramics or the base glass for preparing the 3D curved glass-ceramics satisfies:
[0179] 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250;
[0180] 18.200≤Li2O / P2O5≤25.500;
[0181] 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.200;
[0182] 1.500≤10×(ZrO2+P2O5) / Li2O≤2.000;
[0183] 4.000≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤6.000;
[0184] 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤5.000;
[0185] 12.200≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.000.
[0186] The present application also provides a method for preparing a 3D curved glass-ceramic, which comprises the following steps:
[0187] (1) heat-treating the aforementioned substrate glass to obtain a prefabricated microcrystalline glass product comprising a lithium silicate crystal phase, a lithium disilicate crystal phase and a petalite crystal phase, and having a crystallinity of not less than 60.00wt%;
[0188] (2) Processing the prefabricated microcrystalline glass product obtained in step (1) into a flat microcrystalline glass sheet of required specifications and dimensions, and heat-bending the obtained flat microcrystalline glass sheet to obtain a 3D curved microcrystalline glass, wherein the 3D curved microcrystalline glass contains a petalite crystalline phase and a lithium disilicate crystalline phase, and the petalite crystalline phase and the lithium disilicate crystalline phase have a higher weight percentage than other crystalline phases present in the microcrystalline glass.
[0189] In some embodiments, the process of preparing 3D curved glass-ceramics of the present application may also include conventional cold working of prefabricated glass-ceramics products (such as bricks) obtained by heat treatment of the substrate glass to obtain a flat glass-ceramics of the desired specifications and dimensions (such as a thickness of 0.2 mm-2.0 mm), followed by the step (2) of hot bending. The cold working treatments here include shaping treatments, slicing treatments, CNC treatments, grinding treatments, polishing treatments, etc. commonly used in the art. Those skilled in the art may select one or more of the above methods to perform cold working on the glass-ceramics according to actual needs.
[0190] In the present application, the hot bending process may be accompanied by further crystallization of the prefabricated microcrystalline glass product, resulting in the crystallinity of the finally prepared 3D curved microcrystalline glass being no less than the crystallinity of the prefabricated microcrystalline glass product.
[0191] In the present application, the crystallinity of the prefabricated microcrystalline glass product obtained by heat treatment of the substrate glass is 60wt%-90wt%, preferably 65wt%-90wt%; the crystallinity of the 3D curved microcrystalline glass obtained by heat bending the prefabricated microcrystalline glass product is 70wt%-99wt%, preferably 80wt%-99wt%.
[0192] In the present application, in the above step (1), the conditions of the heat treatment can be selected in a wide range, and those skilled in the art can select from the existing technology according to actual needs. In some embodiments, in step (1), the heat treatment includes nucleation treatment and crystallization treatment, wherein the temperature of the nucleation treatment is (Tg-20°C) to (Tg+40°C), the time of the nucleation treatment is 0min-6000min, the temperature of the crystallization treatment is (T1-50°C) to T1, and the time of the crystallization treatment is 30min-6000min; Tg is the glass transition temperature of the substrate glass, and T1 is the first exothermic peak temperature in the DSC curve of the substrate glass heating; in step (1), the heating rate of the heat treatment process is 5°C / min-15°C / min. It should be understood that in the present application, the nucleation treatment is to heat up to the specified nucleation treatment temperature (also called nucleation temperature), and after reaching the nucleation treatment temperature, keep warm for a certain time, and the insulation time here is the nucleation treatment time (also called nucleation time). The crystallization treatment is to heat up to a prescribed crystallization treatment temperature (also called crystallization temperature), and after reaching the crystallization treatment temperature, keep the temperature for a certain period of time, where the holding time is the crystallization treatment time (also called crystallization time). The above heat treatment process conditions are conducive to obtaining a prefabricated microcrystalline glass product having a specific microstructure and a uniform structure, which can be used for hot bending treatment to obtain a 3D curved microcrystalline glass with petalite crystal phase and lithium disilicate crystal phase as the main crystal phase and excellent optical and mechanical properties.
[0193] In some embodiments, in step (1), the heat treatment includes nucleation treatment and crystallization treatment, wherein the temperature of the nucleation treatment is (Tg-20°C) to (Tg+40°C), for example, (Tg-20°C), (Tg-15°C), (Tg-10°C), (Tg-5°C), (Tg-2°C), Tg, (Tg+2°C), (Tg+5°C), (Tg+10°C), (Tg+15°C) or (Tg+40°C), or any value between these adjacent point values. Wherein, Tg is the glass transition temperature of the substrate glass.
[0194] In some embodiments, in step (1), the time of nucleation treatment is 30 min-360 min, for example, it can be 30 min, 50 min, 70 min, 100 min, 130 min, 150 min, 180 min, 200 min, 250 min, 280 min, 300 min, 330 min, 360 min, 600 min, 1000 min, 2000 min, 3000 min, 4000 min, 5000 min or 6000 min, or any value between these adjacent point values.
[0195] In some embodiments, in step (1), the temperature of the crystallization treatment is ((T1-50°C) to T1, for example, it can be (T1-50°C), (T1-45°C), (T1-40°C), (T1-35°C), (T1-30°C), (T1-25°C), (T1-20°C), (T1-15°C), (T1-10°C), (T1-5°C) or T1, or any value between these adjacent point values.
[0196] In some embodiments, in step (1), the crystallization treatment time is 30 min-600 min, for example, it can be 30 min, 50 min, 70 min, 100 min, 130 min, 150 min, 180 min, 200 min, 250 min, 280 min, 300 min, 330 min, 360 min, 400 min, 450 min, 500 min, 550 min, 600 min, 1000 min, 2000 min, 3000 min, 4000 min, 5000 min or 6000 min, or any value between these adjacent point values.
[0197] In some embodiments, in step (1), the heating rate of the heat treatment process is 5°C / min-15°C / min, for example, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min or 15°C / min, or any value between these adjacent point values. Here, the "heating rate" includes the heating rate of the entire heat treatment process, that is, the heating rate of the nucleation process and the heating rate of the crystallization process.
[0198] In some embodiments, in the above step (2), the hot bending process includes at least 3 preheating stations, at least 3 hot pressing stations and at least 3 cooling stations; the temperature of the preheating station is 500°C-850°C, the temperature of the hot pressing station is 700°C-900°C, the pressure of the hot pressing station is 0MPa-1MPa, and the temperature of the cooling station is 500°C-800°C. The conditions (such as temperature, pressure) of each preheating station, each hot pressing station or each cooling station described in this application are the same or different, for example, the temperature of each preheating station is the same or different.
[0199] In some embodiments, the temperature of the preheating station is 500°C-850°C, for example, 500°C, 600°C, 700°C, 800°C or 850°C, or any value between these adjacent point values.
[0200] In some embodiments, the temperature of the hot pressing station is 700° C.-900° C., for example, 700° C., 750° C., 800° C., 850° C. or 900° C., or any value between these adjacent point values.
[0201] In some embodiments, the pressure of the hot pressing station is 0 MPa-1 MPa, for example, it can be 0 MPa, 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa or 1 MPa, or any value between these adjacent point values.
[0202] In some embodiments, the temperature of the cooling station is 500°C-800°C, for example, 500°C, 600°C, 700°C, 800°C or 850°C, or any value between these adjacent point values.
[0203] In some embodiments, the working time of the preheating station is 90s-360s, the working time of the hot pressing station is 90s-360s, and the working time of the cooling station is 90s-360s. The working time of each station is 90s-360s, for example, it can be 90s, 100s, 110s, 150s, 200s, 250s, 300s, 350s or 360s, or any value between these adjacent point values.
[0204] The present application also provides a chemically strengthened glass-ceramic, wherein the composition at the center of the chemically strengthened glass-ceramic is substantially the same as the composition of the 3D curved glass-ceramic, the chemically strengthened glass-ceramic includes a compressive stress layer region extending from the surface of the chemically strengthened glass-ceramic to a compression depth, and has tensile stress inside the chemically strengthened glass-ceramic.
[0205] It should be understood that after the chemical strengthening treatment, the composition of the surface of the glass-ceramic may be different from the composition of the newly formed glass-ceramic (i.e., the glass-ceramic has not undergone an ion exchange process before the chemical strengthening treatment). This is because during the chemical strengthening treatment, ion exchange occurs on the surface of the glass-ceramic, and one type of alkali metal ion (e.g., Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced by, such as Na in glass-ceramics + K in molten salt bath + Exchange, K + Replaced by, and / or, Li in glass-ceramics + With Na in molten salt bath + Exchange, by Na + However, in the embodiment, the composition of the glass-ceramic at the center of the depth of the glass product or near the center of the depth will still have the composition of the newly formed glass-ceramic. That is, in the chemically strengthened glass-ceramic of the present application, the composition of the compressive stress layer formed by ion exchange on the surface may be different from the composition of the unstrengthened 3D curved glass-ceramic, and the composition at the center of the chemically strengthened glass-ceramic with tensile stress (also called tensile stress) inside will still have the composition of the unstrengthened glass-ceramic.
[0206] In this application, the chemical strengthening treatment conditions used in the preparation of chemically strengthened glass-ceramics from 3D curved glass-ceramics are relatively wide, and those skilled in the art can choose according to actual needs. For example, in some embodiments, the salt bath for chemical strengthening treatment is a mixed molten salt, and the composition of the mixed molten salt includes: 0<NaNO3<100wt%, 0<KNO3<100wt% and 0<LiNO3≤0.2wt%. In some embodiments, the temperature of the salt bath for chemical strengthening treatment is 430℃-530℃, and the time of chemical strengthening treatment is 0.5h-15.0h.
[0207] In some embodiments, the chemically strengthened glass-ceramics has a CS_50 of 110-200 MPa, where CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened glass-ceramics. The range of CS_50 of the chemically strengthened glass-ceramics is within the above range, indicating that the compressive stress of the chemically strengthened glass-ceramics at a depth of 50 μm from the surface is high, indicating that the chemically strengthened glass-ceramics has a higher surface stress level, and the higher the surface compressive stress level, the more residual energy of the drop collision can be offset, thereby ensuring that it has excellent damage resistance.
[0208] In some embodiments, the compressive stress layer depth DOL_0 of the chemically strengthened glass-ceramics is 0.18t-0.25t, where t is the thickness of the chemically strengthened glass-ceramics. The DOL_0 of the chemically strengthened glass-ceramics is within the above range, indicating that the chemically strengthened glass-ceramics has a high compressive stress layer depth, which is more conducive to offsetting the energy driving crack expansion, thereby ensuring that it has excellent damage resistance.
[0209] In some embodiments, the chemically strengthened glass-ceramics has a |CT_AV| of 84-140MPa, where |CT_AV| refers to the absolute value of the average tensile stress. For example, the chemically strengthened glass-ceramics has a |CT_AV| of 84-140MPa, 85-140MPa, 85-120MPa, 85-100MPa, 90-140MPa, 100-140MPa, or 120-140MPa. The |CT_AV| of the chemically strengthened glass-ceramics is within the above range, indicating that the chemically strengthened glass-ceramics has a higher tensile stress level, reflecting that it has a higher surface stress level, and the higher surface compressive stress level can offset the more residual energy of the drop collision, thereby ensuring that it has excellent damage resistance.
[0210] Meeting specific stress characteristics can ensure that chemically strengthened glass-ceramics has excellent mechanical strength properties, especially excellent drop resistance.
[0211] In some embodiments, the chemically strengthened glass-ceramics with a thickness of 0.6 mm is subjected to multiple fixed-point height drop tests using 120-grit sandpaper, and the fixed-point height of the test is 1.0 m. The number of times the chemically strengthened glass-ceramics is dropped to break is ≥30, preferably ≥50. This indicates that the chemically strengthened glass-ceramics of the present application have excellent anti-drop performance.
[0212] In some embodiments, the surface Na2O concentration of the chemically strengthened glass-ceramics is 5.0wt%-20.0wt%. For example, the surface Na2O concentration of the chemically strengthened glass-ceramics can be 5.0wt%, 6.0wt%, 7.0wt%, 8.0wt%, 9.0wt%, 10.0wt%, 11.0wt%, 12.0wt%, 13.0wt%, 14.0wt%, 15.0wt%, 16.0wt%, 17.0wt%, 18.0wt%, 19.0wt% or 20.0wt%, or can be a value within a numerical range consisting of any two of the above specific values as endpoints. By satisfying the surface Na2O concentration within the above range, it can not only ensure that the chemically strengthened glass-ceramics has a better surface stress level, but also ensure that the chemically strengthened glass-ceramics has better weather resistance and chemical durability.
[0213] The 3D curved glass-ceramics or chemically strengthened glass-ceramics with excellent optical and mechanical properties provided in the present application can be used in any glass device of required glass-ceramics and can be used in many applications.
[0214] The present application also provides a glass device, wherein the glass device comprises the 3D curved microcrystalline glass or the chemically strengthened microcrystalline glass.
[0215] The present application also provides an electronic device, wherein the electronic device includes the 3D curved microcrystalline glass or the chemically strengthened microcrystalline glass.
[0216] The following detailed description of the embodiments of the present application is illustrative and is only used to explain the present application, and should not be construed as limiting the present application. In the example number of the following table, S refers to an embodiment, such as S1 refers to embodiment 1; D refers to a comparative example, such as D1 refers to comparative example 1.
[0217] Example 1
[0218] (1) Preparation of substrate glass: The raw materials are prepared according to the ratio of each oxide in S1 of Table 1, and the substrate glass is produced by continuous melting method to obtain substrate glass (brick) with a molding size of 360 mm (length) × 180 mm (width) × 30 mm (thickness). Table 2 is the calculation results of the relationship between the contents of each oxide in Table 1.
[0219] Test results of the substrate glass obtained in S1:
[0220] Ⅰ. Through observation, the substrate glass prepared in S1 is overall clear and transparent.
[0221] II. Determine the Tg and heating DSC curve of the substrate glass in S1, and record the first exothermic peak temperature T1, the second exothermic peak temperature T2 and their difference data in the heating DSC curve, as shown in Table 3, Figure 1 As shown, no exothermic peak or endothermic peak appears under the temperature conditions not involved.
[0222] III. In T g -T2 temperature range, the upper limit temperature of precipitation of lithium silicate crystal phase in the substrate glass obtained by testing T max (Li2SiO3) and the precipitation upper limit temperature of the quartz crystal phase in the matrix glass T max (SiO2), T max (Li2SiO3), T max (SiO2) are shown in Table 3, where T g is the glass transition temperature of the substrate glass.
[0223] (2) Preparation of prefabricated microcrystalline glass: Using a heat treatment roller kiln line, the base glass is subjected to a heat treatment process to produce prefabricated microcrystalline glass bricks. The heat treatment process is shown in Table 4, including a nucleation treatment and a crystallization treatment (referred to as heat treatment process C) performed in sequence. The heating rate of the heat treatment process is 10°C / min. After being taken out of the furnace, the prefabricated microcrystalline glass bricks are obtained.
[0224] Test results of the prefabricated glass-ceramic bricks obtained in S1:
[0225] Ⅰ. Through observation, the microcrystalline glass bricks obtained in S1 are clear and transparent as a whole.
[0226] Ⅱ. The crystal phase composition, crystal phase content and crystallinity of the prefabricated microcrystalline glass were tested. The results are shown in Table 4.
[0227] III. The extreme values of b values at nine locations on the main surface of the prefabricated microcrystalline glass with test dimensions of 360 mm (length) × 180 mm (width) × 30 mm (thickness) are shown in Table 4.
[0228] (3) Cold processing the prefabricated microcrystalline glass bricks: The prefabricated microcrystalline glass bricks are subjected to cold processing, and the cold processing includes shaping, slicing, CNC processing, grinding, and polishing in sequence to obtain a flat microcrystalline glass sheet with a size of 170 mm (length) × 80 mm (width) × 0.6 mm (thickness). The range of the b value at nine locations on the main surface of the obtained flat microcrystalline glass sheet and the average value of the b value at nine locations are tested. The results are shown in Table 4.
[0229] (4) Preparation of 3D curved microcrystalline glass: The obtained flat microcrystalline glass sheet is placed on a 3D hot bending machine for hot bending treatment to form a 3D curved microcrystalline glass. The hot bending machine used in this process is divided into three temperature zones: preheating zone, hot pressing zone and slow cooling zone. The hot bending process (referred to as hot bending process C1) includes 3 preheating stations, 3 hot pressing stations and 3 cooling stations; the temperatures of the 3 preheating stations are 590°C, 680°C and 790°C respectively, the temperatures and pressures of the 3 hot pressing stations are 790°C / 0.4MPa, 790°C / 0.4MPa and 790°C / 0.2MPa respectively, the temperatures of the 3 cooling stations are 790°C, 650°C and 600°C respectively; the residence time of each station is 90s.
[0230] Test results of 3D curved glass-ceramics obtained from S1:
[0231] Ⅰ. Test the optical properties of the 3D curved glass-ceramics, including the extreme difference of the b value at nine locations on the main surface of the 3D curved glass-ceramics sample and the average value of the b value at nine locations. The test results are shown in Table 4.
[0232] II. The crystal phase composition in the 3D curved glass-ceramics was tested, and the results are shown in Table 4. According to calculations, the average crystal size in the 3D curved glass-ceramics is 19 nm.
[0233] III. Testing the XRD diffraction curves of the 3D curved glass-ceramic sheet at the nine b-value tests, the comparison is as follows: Fig.10 As shown. Fig.10 It can be seen that in the microcrystalline glass sheet, there is basically no difference in the crystal phase structure at the position of the maximum b value and the position of the minimum b value on the main surface, or the difference is very small, which indicates that the 3D curved microcrystalline glass sheet is relatively uniform as a whole and the optical display effect tends to be consistent.
[0234] IV. Test the transmittance of the 3D curved glass-ceramic. Fig.13 As shown, it can be seen that the 3D curved microcrystalline glass of the present application has high transmittance in the visible light band and excellent light transmittance.
[0235] (5) Preparation of chemically strengthened glass-ceramics: The 3D curved glass-ceramics with dimensions of 170 mm (length) × 80 mm (width) × 0.6 mm (thickness) obtained in step (4) was placed in a mixed nitrate salt bath of 70.00 wt% KNO3 + 30.00 wt% NaNO3 + 0.03 wt% LiNO3 (here it means based on the total amount of NaNO3 and KNO3 in the mixed molten salt, the mixed molten salt contains 0.03 wt% LiNO3) at 470°C for 7.0 h to obtain chemically strengthened glass-ceramics, t = 0.6 mm.
[0236] Tests on the chemically strengthened glass-ceramics obtained in S1: CS_50, |CT_AV|, and DOL_0 of the chemically strengthened glass-ceramics were tested using a stress tester. The obtained chemically strengthened glass-ceramics were tested for drop resistance at a fixed height of 1.0 m using 120-grit sandpaper; the test data are shown in Table 5.
[0237] Example 2 to Example 13
[0238] The hot bending process is the same as that of Example 1, except that the raw material composition of each example and its corresponding test results are shown in Tables 1 to 5, respectively.
[0239] The 3D curved glass-ceramics of Examples 2 to 13 all meet the following requirements: the overall appearance is clear and transparent; the crystalline phases of the 3D curved glass-ceramics are mainly Li2Si2O5, LiAlSi4O 10 , there is no quartz crystal phase. According to calculation, the average crystal size in the 3D curved glass-ceramics of Examples 2 to 13 is 10-50nm.
[0240] The XRD diffraction pattern of the substrate glass of Example 2 obtained after the heat treatment process C before hot bending is as follows: Figure 8 The temperature rise DSC curve of the substrate glass of Example 10 is shown as follows: Figure 2 shown.
[0241] Comparative Example 1-Comparative Example 13
[0242] The hot bending process was carried out with reference to Example 1, except that the raw material compositions of each comparative example and the corresponding test results were shown in Tables 6 to 11, respectively.
[0243] Among them, the temperature rise DSC curve of comparative example 1 is as follows Figure 3 The temperature rise DSC curve of Comparative Example 2 is shown as Figure 4 As shown, the XRD diffraction pattern of the substrate glass of Comparative Example 2 after heat treatment process C is as follows Fig. 9 As shown. In the nine b-value tests of the microcrystalline glass sheet of Comparative Example 6, the XRD diffraction curves at the maximum b-value position and the minimum b-value position are compared. Fig.11 As shown in the figure, it can be seen that the crystal phase structure at the maximum b value position and the minimum b value position of the main surface of the 3D curved microcrystalline glass sheet is obviously different, which indicates that the microstructure of different areas of the 3D curved microcrystalline glass sheet is inconsistent, which will lead to differences in its overall display effect, resulting in local color display and / or overall color display unevenness on the main surface. The prefabricated microcrystalline glass of Comparative Example 7 cracked during the 3D hot bending process, such as Fig.12 shown.
[0244] After calculation, the average crystal size in the 3D curved glass-ceramics of Comparative Examples 1 to 12 is greater than 20 nm.
[0245] Table 1
[0246]
[0247]
[0248] Table 2
[0249]
[0250] Table 3
[0251]
[0252]
[0253] Note: “ / ” in Table 3 means that there is no SiO2 crystal phase, so there is no quartz vanishing temperature; the meanings in the corresponding table of the comparative examples are the same.
[0254]
[0255]
[0256]
[0257] Table 6
[0258]
[0259] Table 7
[0260]
[0261]
[0262] Table 8
[0263]
[0264] Table 9
[0265]
[0266]
[0267] Table 10
[0268]
[0269]
[0270] Table 11
[0271]
[0272] It can be seen from the examples of Tables 1 to 5 and the comparative examples of Tables 6 to 11 above that, relative to the comparative examples, the embodiment scheme of the present application, while satisfying the content range of each oxide, also satisfies: 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250, 18.200≤Li2O / P2O5≤25.500, 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.200, 1.500≤ ≤10×(ZrO2+P2O5) / Li2O≤2.000, 4.000≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤6.000, 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤5.000, 12.200≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.000. The large-size substrate glass bricks prepared have a clear and transparent appearance, and T max (Li2SiO3)≥T max (SiO2) is conducive to 3D hot bending forming of 3D curved microcrystalline glass with good and uniform optical properties. The heating DSC curve of the substrate glass tested by synchronous thermal analysis has at least two exothermic peaks at a suitable temperature.
[0273] The prefabricated microcrystalline glass bricks obtained by heat treatment of the large-size substrate glass bricks prepared by the embodiments of the present application are also transparent and clear in appearance. The b-value difference of different areas on the main surface of the prefabricated microcrystalline glass brick is small, the uniformity is good, and the prefabricated microcrystalline glass does not contain quartz crystal phase. In the 3D curved microcrystalline glass prepared by heat bending the prefabricated microcrystalline glass, the range of the b-values at nine locations on the main surface is low and the average b-value is also low, which indicates that the 3D curved microcrystalline glass has excellent optical properties and good display effects. At the same time, the obtained 3D curved microcrystalline glass is chemically strengthened to obtain chemically strengthened microcrystalline glass with higher CS_50, |CT_AV|, and DOL_0.
[0274] In the solutions of Comparative Examples 1 to 8 and 12, the formula of the substrate glass does not simultaneously meet the following requirements: the content range of each oxide in the present application, as well as 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250, 18.200≤Li2O / P2O5≤25.500, 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.200, 1 .500≤10×(ZrO2+P2O5) / Li2O≤2.000, 4.000≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤6.000, 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤5.000, 12.200≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.000. When the large-size substrate glass bricks prepared by these schemes are heat-treated to prepare large-size prefabricated microcrystalline glass bricks, the b values of different areas on the main surface of the obtained prefabricated microcrystalline glass bricks are quite different, and this large difference is carried over to the 3D curved microcrystalline glass obtained by hot bending, resulting in poor optical properties, resulting in the display effect of the 3D curved microcrystalline glass not meeting the use requirements, and even cracking.
[0275] In the schemes of Comparative Examples 9 and 10, after preparing large-sized substrate glass bricks, milky white precipitates appeared directly in the substrate glass bricks, the optical properties deteriorated, and the transmittance decreased. In the schemes of Comparative Examples 11 and 12, the mass-produced microcrystalline glass could not achieve the required excellent mechanical properties after chemical strengthening treatment, and the anti-drop effect was significantly worse than that of the product of the present application. In the scheme of Comparative Example 13, milky white precipitates and undissolved matter appeared in the prepared large-sized substrate glass bricks.
[0276] The preferred embodiments of the present application are described in detail above, but the present application is not limited thereto. Within the technical concept of the present application, the technical solution of the present application can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed in the present application and belong to the protection scope of the present application.
Claims
1. A 3D curved glass-ceramic, characterized in that: The 3D curved glass-ceramics contains a petalite crystal phase and a lithium disilicate crystal phase, wherein the petalite crystal phase and the lithium disilicate crystal phase have a higher weight percentage than other crystal phases present in the 3D curved glass-ceramics; the 3D curved glass-ceramics is transparent in the visible light range; Measured in terms of molar percentage of oxides, the composition of the 3D curved glass-ceramics includes: SiO2: 61.00mol%-71.00mol%, Al2O3: 1.50 mol%-5.00 mol%, P2O5: 0.80mol%-1.50 mol%, ZrO2: 2.00 mol%-4.00 mol%, Na2O: 0.00 mol%-1.00 mol%, K2O: 0.00 mol%-0.50mol%, Li2O: 20.00 mol%-30.00 mol%, CaO: 0.00 mol%-1.60 mol%, B2O3: 0.00 mol%-1.00 mol%; The composition of the 3D curved glass-ceramics satisfies the following conditions, measured by the content of each oxide in the composition of the 3D curved glass-ceramics expressed in molar percentage: 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250; 18.200≤Li2O / P2O5≤25.500; 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.200; 1.500≤10×(ZrO2+P2O5) / Li2O≤2.000; 4.000≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤6.000; 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤5.000; 12.200≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.
000.
2. The 3D curved glass-ceramics according to claim 1, characterized in that: The transmittance of the 0.6 mm thick 3D curved glass-ceramics in the visible light range is not less than 90%; and / or, when the thickness of the 3D curved glass-ceramics is 0.6 mm, the haze is ≤0.20%.
3. The 3D curved glass-ceramic according to claim 1, characterized in that: Measured in terms of molar percentage of oxides, the composition of the 3D curved glass-ceramics includes: SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: not less than 0.85mol% and less than 1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: greater than 0.00mol% and not more than 1.00mol%, K2O: greater than 0.00mol% and not more than 0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: greater than 0.50mol% and not more than 1.50mol%, B2O3: 0.00mol%-1.00mol%.
4. The 3D curved glass-ceramic according to any one of claims 1 to 3, characterized in that: The 3D curved glass-ceramics does not contain a quartz crystal phase.
5. The 3D curved glass-ceramic according to any one of claims 1 to 3, characterized in that: In the 3D curved glass-ceramics, the total content of petalite crystal phase and lithium disilicate crystal phase accounts for more than 60.00 wt % of the mass of the 3D curved glass-ceramics; in the 3D curved glass-ceramics, the average crystal size does not exceed 100 nm.
6. The 3D curved glass-ceramic according to claim 5, characterized in that: In the 3D curved glass-ceramics, the total content of the petalite crystal phase and the lithium disilicate crystal phase accounts for more than 70.00wt% of the mass of the 3D curved glass-ceramics.
7. The 3D curved glass-ceramics according to claim 6, characterized in that: In the 3D curved glass-ceramics, the total content of the petalite crystal phase and the lithium disilicate crystal phase accounts for more than 80.00wt% of the mass of the 3D curved glass-ceramics.
8. The 3D curved glass-ceramics according to claim 4, characterized in that: In the 3D curved glass-ceramics, the total content of petalite crystal phase and lithium disilicate crystal phase accounts for more than 60.00 wt % of the mass of the 3D curved glass-ceramics; in the 3D curved glass-ceramics, the average crystal size does not exceed 100 nm.
9. The 3D curved glass-ceramics according to any one of claims 1 to 3, characterized in that: In terms of the content expressed as a molar percentage of each oxide in the composition of the 3D curved glass-ceramics, the composition of the glass-ceramics satisfies: 0.184≤5×P2O5 / (Li2O+0.5Al2O3)≤0.245; and / or 18.200≤Li2O / P2O5≤25.000; and / or 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.180; and / or 1.500≤10×(ZrO2+P2O5) / Li2O≤1.900; and / or 4.200≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤5.900; and / or 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤4.950; and / or 15.000≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.
000.
10. The 3D curved glass-ceramic according to claim 4, characterized in that: In terms of the content expressed as a molar percentage of each oxide in the composition of the 3D curved glass-ceramics, the composition of the glass-ceramics satisfies: 0.184≤5×P2O5 / (Li2O+0.5Al2O3)≤0.245; and / or 18.200≤Li2O / P2O5≤25.000; and / or 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.180; and / or 1.500≤10×(ZrO2+P2O5) / Li2O≤1.900; and / or 4.200≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤5.900; and / or 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤4.950; and / or 15.000≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.
000.
11. The 3D curved glass-ceramic according to claim 5, characterized in that: In terms of the content expressed as a molar percentage of each oxide in the composition of the 3D curved glass-ceramics, the composition of the glass-ceramics satisfies: 0.184≤5×P2O5 / (Li2O+0.5Al2O3)≤0.245; and / or 18.200≤Li2O / P2O5≤25.000; and / or 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.180; and / or 1.500≤10×(ZrO2+P2O5) / Li2O≤1.900; and / or 4.200≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤5.900; and / or 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤4.950; and / or 15.000≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.
000.
12. The 3D curved glass-ceramics according to any one of claims 1 to 3, characterized in that: The composition of the 3D curved glass-ceramics satisfies the following conditions, measured by the content of each oxide in the composition of the 3D curved glass-ceramics expressed in molar percentage: 0.186≤5×P2O5 / (Li2O+0.5Al2O3)≤0.243; and / or 18.500≤Li2O / P2O5≤24.700; and / or 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.170; and / or 1.550≤10×(ZrO2+P2O5) / Li2O≤1.850; and / or 4.600≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤5.850; and / or 2.680≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤4.930; and / or 16.000≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.
000.
13. The 3D curved glass-ceramic according to any one of claims 1 to 3, characterized in that: When the thickness is 0.6 mm, the optical b value of the 3D curved glass-ceramics is ≤1.
00.
14. The 3D curved glass-ceramic according to claim 13, characterized in that: When the thickness is 0.6 mm, the optical b value of the 3D curved glass-ceramics is ≤0.
70.
15. The 3D curved glass-ceramic according to claim 14, characterized in that: When the thickness is 0.6 mm, the optical b value of the 3D curved glass-ceramics is ≤0.
55.
16. The 3D curved glass-ceramic according to claim 4, characterized in that: When the thickness is 0.6 mm, the optical b value of the 3D curved glass-ceramics is ≤1.
00.
17. The 3D curved glass-ceramic according to claim 5, characterized in that: When the thickness is 0.6 mm, the optical b value of the 3D curved glass-ceramics is ≤1.
00.
18. The 3D curved glass-ceramic according to claim 9, characterized in that: When the thickness is 0.6 mm, the optical b value of the 3D curved glass-ceramics is ≤1.
00.
19. The 3D curved glass-ceramic according to any one of claims 1 to 3, characterized in that: When the thickness is 0.6 mm, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics is ≤0.30; The nine locations are: (1) four test locations of test circle I close to the four corners of the main surface; (2) four test locations of test circle II formed by the points on the line segment formed by the centers of the four test circles I that are closest to the middle of the long side or short side of the main surface; (3) one test circle III formed by the center point of the main surface.
20. The 3D curved glass-ceramics according to claim 19, characterized in that: When the thickness is 0.6 mm, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics is ≤0.
10.
21. The 3D curved glass-ceramic according to claim 20, characterized in that: When the thickness is 0.6 mm, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics is ≤0.
06.
22. The 3D curved glass-ceramics according to claim 4, characterized in that: When the thickness is 0.6 mm, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics is ≤0.30; The nine locations are: (1) four test locations of test circle I close to the four corners of the main surface; (2) four test locations of test circle II formed by the points on the line segment formed by the centers of the four test circles I that are closest to the middle of the long side or short side of the main surface; (3) one test circle III formed by the center point of the main surface.
23. The 3D curved glass-ceramics according to claim 5, characterized in that: When the thickness is 0.6 mm, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics is ≤0.30; The nine locations are: (1) four test locations of test circle I close to the four corners of the main surface; (2) four test locations of test circle II formed by the points on the line segment formed by the centers of the four test circles I that are closest to the middle of the long side or short side of the main surface; (3) one test circle III formed by the center point of the main surface.
24. The 3D curved glass-ceramics according to claim 9, characterized in that: When the thickness is 0.6 mm, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics is ≤0.30; The nine locations are: (1) four test locations of test circle I close to the four corners of the main surface; (2) four test locations of test circle II formed by the points on the line segment formed by the centers of the four test circles I that are closest to the middle of the long side or short side of the main surface; (3) one test circle III formed by the center point of the main surface.
25. The 3D curved glass-ceramics according to claim 13, characterized in that: When the thickness is 0.6 mm, the range of the b values at nine locations on the main surface of the 3D curved glass-ceramics is ≤0.30; The nine locations are: (1) four test locations of test circle I close to the four corners of the main surface; (2) four test locations of test circle II formed by the points on the line segment formed by the centers of the four test circles I that are closest to the middle of the long side or short side of the main surface; (3) one test circle III formed by the center point of the main surface.
26. A substrate glass, which can be used to prepare the 3D curved glass-ceramics according to any one of claims 1 to 25, characterized in that: The composition of the substrate glass includes, in terms of molar percentage of oxides: SiO2: 61.00mol%-71.00mol%, Al2O3: 1.50 mol%-5.00 mol%, P2O5: 0.80mol%-1.50 mol%, ZrO2: 2.00 mol%-4.00mol%, Na2O: 0.00 mol%-1.00 mol%, K2O: 0.00 mol%-0.50 mol%, Li2O: 20.00 mol%-30.00 mol%, CaO: 0.00 mol%-1.60 mol%, B2O3: 0.00 mol%-1.00 mol%; The composition of the substrate glass satisfies the following conditions, expressed in terms of the molar percentage of each oxide in the substrate glass composition: 0.180≤5×P2O5 / (Li2O+0.5Al2O3)≤0.250; 18.200≤Li2O / P2O5≤25.500; 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤2.200; 1.500≤10×(ZrO2+P2O5) / Li2O≤2.000; 4.000≤(SiO2-7Al2O3-Li2O) / (P2O5+ZrO2)≤6.000; 2.600≤99×(CaO+ZrO2) / (Li2O+Na2O+1000K2O)≤5.000; 12.200≤(5.6B2O3+10Al2O3+6.5CaO) / ZrO2≤20.
000.
27. The substrate glass according to claim 26, characterized in that: According to the synchronous thermal analysis test, under the protective atmosphere of nitrogen, the substrate glass is heated from room temperature to 900°C at a heating rate of 10°C / min to obtain a heating DSC curve. In the heating DSC curve, there are at least two exothermic peaks, wherein the first exothermic peak temperature T1 is 600°C-730°C, and the second exothermic peak temperature T2 is 740°C-800°C, and T1 and T2 satisfy the relationship: 100°C ≥ T2-T1 ≥ 40°C.
28. The substrate glass according to claim 27, characterized in that: 80℃≥T2-T1≥50℃.
29. The substrate glass according to claim 27, characterized in that: In T g -T2 temperature range, the upper limit temperature T of the precipitation of a lithium silicate crystal phase in the substrate glass is tested. max (Li2SiO3) and the precipitation upper limit temperature of the quartz crystal phase in the matrix glass T max (SiO2), T max (Li2SiO3) ≥ T max (SiO2), where T g is the glass transition temperature of the substrate glass.
30. The substrate glass according to any one of claims 26 to 29, characterized in that: The composition of the substrate glass includes, in terms of molar percentage of oxides: SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: not less than 0.85mol% and less than 1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: greater than 0.00mol% and not more than 1.00mol%, K2O: greater than 0.00mol% and not more than 0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: greater than 0.50mol% and not more than 1.50mol%, B2O3: 0.00mol%-1.00mol%.
31. A method for preparing a 3D curved glass-ceramic according to any one of claims 1 to 25, characterized in that: The steps include: (1) heat-treating the substrate glass according to any one of claims 26 to 30 to obtain a prefabricated microcrystalline glass product comprising a lithium silicate crystal phase, a lithium disilicate crystal phase and a petalite crystal phase, and having a crystallinity of not less than 60.00wt%; (2) Processing the prefabricated microcrystalline glass product obtained in step (1) into a flat microcrystalline glass sheet of required specifications and dimensions, and heat-bending the obtained flat microcrystalline glass sheet to obtain a 3D curved microcrystalline glass, wherein the 3D curved microcrystalline glass contains a petalite crystal phase and a lithium disilicate crystal phase, and the petalite crystal phase and the lithium disilicate crystal phase have a higher weight percentage than other crystal phases present in the 3D curved microcrystalline glass.
32. The method for preparing 3D curved glass-ceramics according to claim 31, characterized in that: In step (1), the heat treatment includes nucleation treatment and crystallization treatment, wherein the temperature of the nucleation treatment is (Tg-20°C) to (Tg+40°C), the time of the nucleation treatment is 0min-6000min, the temperature of the crystallization treatment is (T1-50°C) to T1, and the time of the crystallization treatment is 30min-6000min; Tg is the glass transition temperature of the substrate glass; in step (1), the heating rate of the heat treatment process is 5°C / min-15°C / min.
33. The method for preparing 3D curved glass-ceramics according to claim 31 or 32, characterized in that: In step (2), the hot bending process includes at least 3 preheating stations, at least 3 hot pressing stations and at least 3 cooling stations; the temperature of the preheating station is 500°C-850°C, the temperature of the hot pressing station is 700°C-900°C, the pressure of the hot pressing station is 0MPa-1MPa, and the temperature of the cooling station is 500°C-800°C.
34. The method for preparing 3D curved glass-ceramics according to claim 33, characterized in that: The working time of each preheating station is 90s-360s, the working time of each hot pressing station is 90s-360s, and the working time of each cooling station is 90s-360s.
35. A chemically strengthened glass-ceramic, characterized in that: The composition at the center of the chemically strengthened glass-ceramic is the same as the composition of the 3D curved glass-ceramic as described in any one of claims 1 to 25, and the chemically strengthened glass-ceramic includes a compressive stress layer region extending from the surface of the chemically strengthened glass-ceramic to the compression depth, and has tensile stress inside the chemically strengthened glass-ceramic.
36. A glass device, characterized in that: The glass device comprises the 3D curved microcrystalline glass as described in any one of claims 1 to 25 or the chemically strengthened microcrystalline glass as described in claim 35.
37. An electronic device, characterized in that: The electronic device comprises the 3D curved microcrystalline glass as described in any one of claims 1 to 25 or comprises the chemically strengthened microcrystalline glass as described in claim 35.
Citation Information
Patent Citations
3D microcrystalline glass, preparation method thereof and pre-crystallized microcrystalline glass
CN115872622A